Why Poverty Mentality Matters for Achieving the First Sustainable Development Goals (SDGs) in Nigeria - James Tumba Henry (Inclusive Society and Sustainability Studies, 2022)
In the past two decades, the effort toward reducing poverty and its dimensions has increased in middle and low-income countries by introducing diverse social protection programmes. In Nigeria, for instance, various successive regimes have experimented with myriads of programmes targeted at poverty alleviation. Yet, in 2018, Nigeria was named the world's poverty capital, with about 87 million citizens living in extreme poverty. This data could be because economists, the World Bank, and other development organizations have stereotyped the concept of poverty as income, consumption, and wealth without paying attention to the "poverty mentality". As a result, governments often instinctively neglect the influence of the "poverty mentality" on the part of beneficiaries of poverty alleviation programmes when initiating social protection policy framework for the country. However, from the literature reviewed, a "poverty mentality" often leads to poor financial decisions and deadweight spending. Accordingly, this research article recommends a new international poverty order (NIPO) by dealing with multidimensional poverty and "poverty mentality" through investment education and value reorientation.